Facile synthesis of 3-(1-(4'-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl)biphenyl-4-yl)-5-oxo-2-phenyl-1H-imidazol-4(5H)-ylidene)indolin-2-ones: β-Lactam derivatives as antimicrobes - Bishnoi, Abha; Srivastava, Krishna; Singh, Suruchi; Tripathi, Chandrakant Mani (European Journal of Chemistry, 2011)
A facile synthesis of b-lactam derivatives; 3-(1-(4'-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl)biphenyl-4-yl)-5-oxo-2-phenyl-1H-imidazol-4(5H)-ylidene)indolin-2-ones (6a-e) and 3-(1-(3-chloro-2-(substituted phenyl)-4-oxoazetidin-1-yl)-5-oxo-2-phenyl-1H-imidazol-4(5H)-ylidene)indolin-2-ones (7a-e) is described herein. The title compounds 6a-e and 7a-e were evaluated for their in vitro antimicrobial activity against Candida albicans and Bacillus subtilis respectively using a two fold serial dilution technique. Investigation revealed that 2-hydroxy phenyl function at b-lactam ring in compounds 6d and 7d is a key factor for both antifungal and antibacterial activity, as newly designed compounds 6d and 7d exhibited good biological activity with minimum inhibitory concentration (MIC)12.5 mg/mL against Candida albicans and Bacillus subtilis respectively.